Relationship between Parental Engagement and Student Achievement of Secondary Level Students - Nepal, Bimal (Journal of Janta Multiple Campus, 2024)
The aim of this research is to study the relationship between parental engagement and student achievement of secondary level students especially grade 10 students in public and private schools in the Sunsari district using survey design through simple random method. Data were collected by pre- prepared and expert standardized Likert scale having structured questionnaires and analyzed descriptively and inferentially through using the SPSS software. This study finds that both parents (father and mothers) of private schools' students are more educated than public schools. This study also finds that fathers and mothers in both schools are the students' Immediate Parents of the grades 10 students. In addition to that, it finds that maximum students of public schools obtained moderate grades (C-C+) whereas good grades (B-B+) in private schools. Thus, the achievement of public schools' student is low than private school's students. Furthermore, there is no significant mean difference between fathers/mothers' qualifications and students' achievement in both public and private schools. It finds that there is a weak, positive and no significant relationship between parents' talks practice and students' achievement and there is negative, weak and significant relationship between reward practice of parents and students' achievement. Likewise, there is also weak, positive and no significant relationship between punishment practice and students' achievement and negative and there is weak and no significant relationship between support practice of parents and students' achievement.